Missed Opportunities and Hasty Decisions: Critical Analysis of Criminal Law Amendment Act, 2018 - Sharma, Abhishek (Trinity Law Review, 2021)
The two barbaric rape cases in Kathua and Unnao shook the conscience of the entire nation. There was a huge public demand for stringent rape laws, which ultimately led to the birth of Criminal law Amendment Act, 2018. Keeping in mind the accelerating rate of sexual offences against women and to ensure women safety, the amendment was the need of the hour, still the amendment missed certain opportunities which were much needed in India and it is high time to acknowledge some changes which are much needed in Indian Criminal Law system dealing with sexual offences in India. This study would focus upon some missed opportunities and some hasty and ill-conceived decisions of the Legislature while dealing with the sexual offences in India in the said amendment. Some of the missed opportunities and hasty and ill-conceived decisions in Criminal Law Amendment Act, 2018: Whether introduction of death penalty in rape cases involving child below 12 years of age is deterrent or is just a myth? Is increasing the punishment from 10 to 20 years, when victim is of age between 12-16 years is justified even if the sexual intercourse is consensual? Punishment under 376(1) is increased from 7 years minimum to 10 years minimum making no difference with cases involving aggravated rape. Is it justified to not give anticipatory bail to a person accused of an offence of rape when victim is below 16 years of age?